Mathematics Anxiety Among Secondary School Students: A Rational Emotive Behaviour Therapy Approach - Egara, Felix O.; Mosimege, Mogege D. (International Journal of Research in Counseling and Education, 2024)
In this study, rational emotive behaviour therapy (REBT) was used to lessen mathematics anxiety which is common among secondary school students. The main aim was to investigate the effect of REBT on mathematics anxiety among students. The study employed a quasi-experimental design with a population of 3 390 senior secondary school one (SS 1) students in Nsukka Education Zone of Enugu State, Nigeria. A total of 115 students formed the sample for this study, determined through GPower software version 3.1. The instrument employed was the Mathematics Anxiety Scale (MAS). Students with a score of 51 were mathematics anxious. The 115 mathematics anxious participants sieved were randomly assigned to experimental and control groups. The intervention lasted for 6 weeks of treatment. The administration of MAS in both groups was done before and after treatment making up pre-test and post-test. Data collected were subjected to analysis using SPSS software that was reported through the mean, standard deviation (SD) and ANCOVA. Results revealed showed REBT had a significant effect on mathematics anxiety among students. It showed further that gender does not influence students’ manifestation of mathematics anxiety when exposed to REBT treatment. It was based on the findings that recommendations were made among others that REBT should be put into use by guidance counsellors in reducing mathematics anxiety among students in Nigeria and across the globe.